Sabah Electricity Sdn. Bhd. : a case study on bad debt analysis and the effect on company expenses / Zulkhairul Ali - Ali, Zulkhairul (2009)
This paper studies on the uncollected bills (bad debt) of SESB and the potential factors influence those uncollected bills (bad debt) of company. To do so the researcher will also examines the impacts of uncollected bills (bad debt) on company’s overall expanses and give suggestions and recommendation to overcome the problems. In this study, the researcher wants to know the impact of uncollected bills (bad debt) on company’s performance especially in expenses. The information is gathered from credit control department where the departments give the write off bad debt for 2007, total overall account cannot be found, total debtors for SESB, total bad debt and sales of SESB. The findings of this study show the uncollected bills (bad debt) for 3 years on financial year 2007 until financial year 2009 and its impacts on company’s expanses.